Formula Optimization of Rifampicin Dry Powder Inhalation with Chitosan-Xanthan Carrier Using Response Surface Methodology - Silvia Surini, Rahmadina Providya, Kurnia Sari Setio Putri (Journal of Applied Pharmaceutical Science, 2019)
This study was aimed to obtain an optimum formula of rifampicin dry powder inhalation (DPI) with chitosan-xanthan (CX) as a carrier by spray drying method using response surface methodology (RSM). Fourteen experimental formulas were designed statistically by Box Behnken method by varying three parameters namely concentration of CX solution, rifampicin/CX ratio, and inlet temperature of the spray dryer. The entrapment efficiency (EE), particle size, and drug release in pH 7.4 (pulmonary condition) and pH 4.5 (pulmonary macrophages condition) of the rifampicin DPI were characterized. The optimum formula of rifampicin DPI was obtained using Design Expert software. The obtained DPI from those 14 formulas possessed EE of 112.00–149.08% and average particle sizes of 0.599–5.506 μm. Rifampicin release in phosphate buffer medium pH 7.4 was 6.54%–22.95% and in pH 4.5 was 12.02–48.60%. The Design Expert predicted that the optimum formula would be obtained with a concentration of CX solution of 0.5%, a ratio of rifampicin to CX 1:1, and inlet temperature of the spray dryer at 143°C. The optimized formula produced a rifampicin DPI with EE of 108.9%, the particle size of 1.177 μm, and the rifampicin release of 14.49% (at pH 7.4) and of 37.97% (at pH 4.5).
Keywords: Chitosan-xanthan, dry powder inhalation, rifampicin, response surface methodology, spray drying.